Clinical features, diagnosis and management of amoxicillin-induced Kounis syndrome - Wang, Chunjiang; Zhou, Yulu; Fang, Weijin; Li, Zuojun; Zhao, Shaoli (Frontiers in Pharmacology, 2022)
Background:The available evidence suggests that amoxicillin is often associated with the occurrence of Kounis syndrome (KS). The purpose of this study is to explore the clinical characteristics of KS induced by amoxicillin. Methods We searched for case reports of amoxicillin-induced KS through Chinese and English databases from 1972 to May 2022. Results A total of 33 patients with KS were included, including 16 patients (48.5%) receiving amoxicillin treatment and 17 patients (51.5%) receiving amoxicillin-clavulanate. The median age was 58 years (range 13-82), 75.8% were from Europe and 81.8% were male. Nearly 70% of KS patients develop symptoms within 30 minutes after administration. Chest pain (63.6%) and allergic reaction (75.8%) were the most common clinical manifestations. Clinical examination included 24 patients (72.7%) with elevated troponin, 27 patients (81.2%) with ST-segment elevation, 15 patients (53.6%) with coronary artery stenosis and thrombosis. Thirty-two (97.0%) patients recovered completely after discontinuation of amoxicillin and treatment.